Outcome of Middle East Respiratory Syndrome (MERS) in hematology and oncology patients: A case series in Saudi Arabia - Ahmed Alaskar; Naila A. Shaheen; Mohammed Bosaeed; Hina Rehan; Mushtaq Rather; Hind Salama; Khadega A. Abuelgasim; Giamal Gmati; Moussab Damlaj; Bader Alahmari; Mohsen Alzahrani; Adel Othman; et al. (Elsevier, 2021)
Background: Middle East Respiratory Syndrome Coronavirus (MERS-CoV) is associated with a high fatality rate (34%), which is higher in the presence of co-morbidities. The aim of the current study was to assess the clinical course and the outcome in hematological or oncological malignancy cases, diagnosed with MERS-CoV. Methods: This is a case series of hematological /oncological cases, diagnosed with MERS-CoV, in a tertiary care setting in 2015. The cases were identified based on the World Health Organization (WHO) MERS-CoV case definition. The demographic, clinical, and outcome data were retrieved from the patients' medical charts and electronic health records. Results: In total, nine hematological or oncological cases were identified, diagnosed with MERS-CoV. The baseline malignant condition was hematological malignancy in seven patients, as well as colon cancer and osteosarcoma in one patient each. Six (67%) patients were male. The median age was 65 years (range 16-80 years). Co-morbidities included chronic kidney disease (n = 3.33%), diabetes mellitus (n = 3.33%), and hypertension (n = 2.22%). The presenting symptoms were shortness of breath (n = 6.66%), fever (n = 5.55%), cough (n = 2.22%), and diarrhea (n = 2.22%). Chest x-rays indicated bilateral infiltrates in 6 patients (66%). The PCR (polymerase chain reaction) test was repeated in six patients to confirm the diagnosis. The mortality rate was 100%, and the median time to death was 26 days (range 15-77 days). Conclusion: MERS-CoV infection in this small cohort of hematology or oncology patients has a 100% mortality rate, regardless of the status of the underlying disease. The confirmation of the diagnosis may require repeated testing. Additional studies are required to verify the findings and to elucidate the disease pathogenesis in cancer patients.